2022
DOI: 10.1186/s13054-022-04270-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on antifungal consumption: a multicenter retrospective analysis

Abstract: Background In the context of COVID-19 pandemic, antifungal overuse may have occurred in our hospitals as it has been previously reported for antibacterials. Methods To investigate the impact of COVID-19 on antifungal consumption, a multicenter retrospective study including four medical sites and 14 intensive care units (ICU) was performed. Antifungal consumption and incidences of invasive fungal diseases before and during COVID-19 pandemic, for non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…For antifungals, our data showed decreased consumption during 2020–2021. This outcome was unexpected since other authors have reported increased incidences of invasive fungal diseases in COVID-19 patients, with voriconazole the first-line treatment [ 36 ]. Nevertheless, we found that the used amount of this antifungal in Portugal displayed a negative rate of −7% for 2020 but a positive rate of 12% for 2021 compared with 2019.…”
Section: Discussionmentioning
confidence: 95%
“…For antifungals, our data showed decreased consumption during 2020–2021. This outcome was unexpected since other authors have reported increased incidences of invasive fungal diseases in COVID-19 patients, with voriconazole the first-line treatment [ 36 ]. Nevertheless, we found that the used amount of this antifungal in Portugal displayed a negative rate of −7% for 2020 but a positive rate of 12% for 2021 compared with 2019.…”
Section: Discussionmentioning
confidence: 95%
“…The recent COVID-19 pandemic and the risk of the patient becoming immunocompromised with a risk of systemic fungal infection highlighted the need for antifungal stewardship programs to prevent and fight unwarranted systemic infections [ 32 , 33 ]. Antifungal consumption during COVID-19 was evidenced to be increased [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recent COVID-19 pandemic and the risk of the patient becoming immunocompromised with a risk of systemic fungal infection highlighted the need for antifungal stewardship programs to prevent and fight unwarranted systemic infections [ 32 , 33 ]. Antifungal consumption during COVID-19 was evidenced to be increased [ 33 , 34 ]. However, a UK study reported that despite the COVID-19 pandemic’s effect on increasing antifungal consumption, the standards of care were good as a result of the presence of technology to facilitate antifungal stewardship programs [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…While most reviews to date have focused on antibacterial use during the COVID-19 pandemic, we hypothesize that the pandemic also impacted the use of antifungal agents in critically ill patients. Limited data from Spain and France found elevation in the use of several mold-active antifungals, including amphotericin B, echinocandins, and voriconazole [ 18 , 19 ]. To date, only a single review analyzed trends of antifungal usage in the United States.…”
Section: Introductionmentioning
confidence: 99%